A Christian Education in the Virtues Character Formation and Human Flourishing - Arthur, James (Routledge Research in Character and Virtue Education, 2021)
A Christian Education in the Virtues examines the connection between human nature and human flourishing. It draws on ancient and medieval sources to explore the formation of the person based on a Christian anthropology, emphasising the communal nature of the virtuous life and provides a richer approach to the question of contemporary character education. The book argues that the only way to understand and construct our character virtues is to have a clear picture of what is the purpose and meaning of human life. It highlights the importance of engaging with moral issues and makes the case that, for Christian educators, human flourishing is inseparable from God's active relationship to human beings. The book also explores a teleological approach to character education goals. To educate the whole person in the light of an all-embracing Christian worldview is challenged by secular and liberal ideology and is often seen as irrational to the modern mind. Overall, the text seeks to demonstrate that many aspects of a Neo-Aristotelian-Thomist theoretical underpinning for Christian character education holds out a viable option for Christians. It therefore argues the case for the educational potential of Christian character education. This important book will be essential reading for academics, researchers and students in the fields of character and virtue education, religious education and the philosophy of education. The Open Access version of this book, available at www.taylorfrancis.com/books/oa-mono/10.4324/9781003141877, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.